Penerapan Alat Peraga Diagram Untuk Meningkatkan Pemahaman Penyajian Data Pada Siswa Kelas VII SMP - Meisya Nazelina; Arvin Efriani; Feli Ramury (GEOMATH, 2026)
This study aimed to determine the effect of diagram teaching aids on students’ understanding of data presentation in seventh-grade students at SMP FITRA ABDI Palembang. The research used a quantitative method with a quasi-experimental design in the form of a posttest-only control group design. The sample consisted of two classes, namely an experimental class and a control class, with 18 students in each class. The experimental class received learning using diagram teaching aids, while the control class used conventional learning methods. Data collection was conducted through a posttest on data presentation material. Data were analyzed using the Shapiro-Wilk normality test, Levene’s homogeneity test, and Independent Samples T-Test assisted by SPSS software. The results showed a significance value of 0.205 > 0.05, indicating no statistically significant difference between the experimental and control classes. However, the experimental class obtained a higher mean score than the control class, namely 74.72 and 68.33. Thus, the use of diagram teaching aids gave a positive descriptive effect on students’ understanding of data presentation